Wind energy potential estimation for the Chernobyl nuclear power plant exclusion zone - Kudria, S.; Tuchynsky, B.; Ivanchenko, I.; Petrenko, K. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2016)
The specificity of the exclusion zone of the Chernobyl nuclear power plant is that in this area there is a deep electric power and road infrastructure is a serious argument in favor of a positive decision on the construction of wind farms. One of those factors that significantly affect the economic efficiency of investment in wind farms and which currently remains uncertain, it is - the wind energy potential of the exclusion zone. This article is a study of this problem. The presence or absence of the required level of wind potential, in this case, is crucial for the decision. In Institute of Renewable Energy NAS of Ukraine available measurements of wind speed at the meteorological station "Chernobyl" for the period 1970-2011 years. A major drawback meteorological weather information "Chernobyl" is no data synchronous measurements of wind speed at two heights, making it impossible simulation of vertical wind profile. Therefore, the article estimates made for the two limiting (in our estimation) values of vertical wind profile - a = 0.14 and a = 0.22. To complete the picture also made the relevant calculations according to the meteorological station "Chernigov-airport" in terms of more open areas at a distance of 66 km from the meteorological station"Chernobyl". The calculation is made for the modern models of wind turbines of 2 MW Vestas V110-2.0 MW rotor axis height of 125 meters, specially designed for sites with low wind speeds (Low-Speed Site). Studies have shown that weather station "Chernobyl" site has a very high level of secrecy wind speed sensor that distorts the true picture of a wind farm site and does not allow for the measurement data to reliably estimate its wind energy potential. Long-term wind speed data in meteorological station located near "Chernigov-airport" evidencing the adjacent territory the wind energy potential, it is sufficient to implement cost-effective wind farm project. There are factors that hypothesis of homogeneity wind regime sites considered in the analysis. To obtain more accurate estimates necessary to study the wind characteristics at the Chornobyl site in accordance with international standards MEASNET and IEC, during which perform thorough micrositting, which resulted in optimizing the location of wind farm site relative impact of local factors.